The art of learning : a self-help manual for students - Ramsland, Katherine M., 1953- (Albany : State University of New York Press, 1992)
Annotation Much has been written for teachers recently on new theories of interactive education; here is a guide for college students. Ramsland (philosophy, Rutgers U.) explains how students can take responsibility for their own education by moving beyond passive processing edition (unseen), $9.95. Annotation copyrighted by Book News, Inc., Portland, OR.
15. Inner Learning: Applications -- 16. Becoming a Master -- BIBLIOGRAPHY -- INDEX -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- V -- W -- Z.
Includes bibliographical references (pages 229-232) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Learning, Psychology of; Thought and thinking; Study skills; Thinking; Psychologie de l'apprentissage.; Pensée.; Étude -- Méthodes.; thinking; EDUCATION -- Educational Psychology; Learning, Psychology of; Study skills; Thought and thinking; Lerntechnik